In Vitro and in Vivo Effects of Aqueous Extract of Rosmarinus officinalis L. (Rosemary) in The Control of Late Blight Disease of Potato Caused by Phytophthora Infestans Mont. De Bary. in Algeria (2015)
The fungus Phytophthora infestans is known to develop resistance against the metalaxyl (fungicide), commonly used in the control of potato mildew disease. There is therefore urgent need to explore the potentials of alternative fungicides which are potent, affordable, readily available, easy to prepare and environment friendly. The study was carried out to test the fungicidal potential of aqueous extracts of Rosmarinusofficinalis (Rosemary), in vitro and in vivo on two isolates of P. infestans collected from two potato producing Algerian areas: Bourkika (Tipaza City) and El Abbadia (Aindefla City). Various concentrations of crude extracts of Rosmarinus officinalis applied by direct contact in the following dilutions: 5%, 10% and 20% on medium with pea-agar (PPA), allowed the inhibition of mycelial growth of P. infestans isolates. The observed rates of inhibition exceeded 85% and the inhibitive minimal concentration (CMI) was 5%. Parallel structural modifications, caused by mycelial lyses, as well as the deformation or, and the digestion of the contents of sporangia affected the morphology of both strains from the lowest concentration. The sporulation and the germination were inhibited by this aqueous extract (100%). Also, the absence of resumption of mycelial growth on medium PPA and absence of the mildew symptoms on detached Spunta potato leaves confirmed the fungicidal effect of the Rosemary aqueous extract. This also translated in vivo as significant reduction of the disease was observed. Disease reduction was recorded for the preventive application modes by spraying with the crude aqueous extract (86.2%) and by watering, while for the curative mode with crude extract (81%). On the other hand, Spunta variety was more marked for preventive mode by watering (85%) and the curative one (90%) also, A2 isolate was more inhibited for the application of R. officinalis aqueous extract by curative (83%), spraying mode (86%) and watering modes. Besides, treatments made in preventive modes by spraying and watering showed a total inhibition of the sporulation (100%), exceeding 85% in Spunta variety and 96% for A1 isolate was observed in the curative mode of application. This study thus confirms the antifungal potential of aqueous extract of Rosmarinus officinalis on P. infestans isolates. It is thus recommended for use as bio-fungicide in the management of potato mildew disease.